Guidelines for safe storage and handling of reactive materials (American Institute of Chemical Engineers, 1995)
With new and growing interest in dealing with the hazards of reactive chemicals, this book offers guidelines that can significantly reduce the risk or mitigate the severity of accidents associated with storing and handling reactive materials. Necessary elements of a reliable system to prevent equipment or human failures that might lead to a reactive chemical incident are sound and responsible management policies, together with a combination of superior siting, design, fabrication, erection, inspection, monitoring, maintenance, operations and maintenance of facilities. These Guidelines deal wit.